PSYCOLOGY FACTORS OF EXPERIENCING OF SUBJECTIVE WELL-BEING BY PSYCHOLOGY STUDENTS - Дубчак, О.; Чубата, Т. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2019)
The experience of well-being is a key element of predominant mood of individual, since the subjective well-being, as integrative, especially significant experience, constantly affects on various parameters of a person’s mental state and, as a result, on successfulness of behavior, productiveness of activity and effectiveness of interpersonal interaction. These feelings (experiences) are major asset of state of social conscience, group moods, expectations and relationships in society. The article identifies factors of subjective well-being of a person, for instance: the category “image” as a conscious way of life or an image of desired goals; the category “motive” as an incentive to achieve individually significant goals or realization of the desired lifestyle; experiences as feelings that “inform” him about his relationship with the environment, as feelings that an individual experiences, comparing his efforts, actions to achieve a desired goal or lifestyle, with all that he achieved in reality or what others people achieve; category of “emotions” as an emotional assessment of oneself, one’s achievements, degree of self-satisfaction and one’s life. It is proven that the majority of psychology students are characterized by life satisfaction, satisfaction with their effectiveness and the process of achieving the goals and capabilities of the present, which indicates a self-confidence, positive self-esteem. A significant number of students believe, that they manage their lives independently and in their strengths and capabilities; they adequately assess their abilities and the results expected from their actions. Depending on the level of subjective well-being, their motivational and value-based structure also changes. An increase in the level of subjective well-being increases the spiritual and moral orientation of students, a decrease in the level of subjective well-being lead to the growth of selfish-prestigious or pragmatic orientation of the motivational-value structure. As pointed out in the article, that during the student years the subjective well-being can be defined as an important indicator of readiness for professional activity and its success, as well as a factor in successful educational activity and a prognostic indicator of future professional productivity and specialist satisfaction